IDENTIFIKASI POTENSI BAHAYA DAN PENGENDALIAN RISIKO KECELAKAAN KERJA PADA PEKERJA KAYU LAPIS PT INDAH KAYU SEJAHTERA - Yosi Aulia; Ayudyah Eka Apsari (JURNAL ILMIAH RESEARCH STUDENT, 2026)
PT Indah Kayu Sejahtera is facing significant occupational safety issues in the plywood production sector due to the complex production process that involves the use of large machinery, hot steam, and sharp tools. Data from the past year, specifically from January 2025 to January 2026, show that there were21 work accident, consisting of 13 minor accident, 7 moderate accident, and 1 severe accident. This study aim to identify potential hazard, assess risk levels, recommed risk controls, and formulate an Occupational Health an Safety (OHS) Standard Operating Procedure (SOP) to minimize the potential for workplace accident in the plywood production process. The methods uses are the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method to manage risks systematically, and the FTA (Fault Tree Analysis) to map the root causes of workplace accident. The result of hazard identification and risk assessment indicate 8 high risks at 8 workstations, 17 medium risks at 10 workstation, and 23 low risks at 13 workstation. FTA analysis of 8 main type of incident (top event) shows that the root causes of accident are dominate by worker negligence and fatigue, lack og training, and non compliance with procedures, damage to machine guards to automatic sensors, as well as low discipline in the use of Personal Protective Equipment (PPE). Based on this research, control measure are formulated comprehensively through engineering control, administrative controls, the use of PPE, and yhe preparation of a stricter new OHS SOP recommendation to reduce workplace accident rates.